Soil physical properties and root activity in a soybean second crop/maize rotation under direct sowing and convenitonal tillage - Barrios, M.B.=700 1 Bozzo, A.A.; Debelis, S.P.; Pereyra, A.M.; Bujan, A.
(Es, En)
ilus., 43 ref.
Keywords: PROPIEDADES FISICO-QUIMICAS SUELO; RENDIMIENTO; ROTACION DE CULTIVOS; SOJA; MAIZ; LABRANZA CONVENCIONAL; ESPAÑA